The Patient's Right to AI: Can I Request an AI Analysis of My Medical Images? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare, particularly medical imaging, has led to a critical question from patients: Can I request that...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care